Subjective social status predicts long-term smoking abstinence - Cofta-Woerpel Ludmila; Mazas Carlos A; Castro Yessenia; Cao Yumei; Li Yisheng; Kendzor Darla E; Businelle Michael S; Reitzel Lorraine R; Cinciripini Paul M; Wetter David W (BMC, 2011)
Abstract Background The relationship between subjective social status (SSS), a person's perception of his/her relative position in the social hierarchy, and the ability to achieve long-term smoking abstinence during a specific quit attempt is unknown. The purpose of this study was to examine the relationship between SSS and long-term smoking abstinence among 421 racially/ethnically diverse smokers undergoing a specific quit attempt, as well as the interactive effects of race/ethnicity and sex. Methods The main effects and moderated relationships of SSS on biochemically-confirmed, continuous smoking abstinence through 26 weeks post-quit were examined using continuation ratio logit models adjusted for sociodemographics and smoking characteristics. Results Even after adjusting for the influence of socioeconomic status and other covariates, smokers endorsing lower SSS were significantly less likely to maintain long-term smoking abstinence during a specific quit attempt than those with higher SSS (OR = 1.14, 95% CI: 1.00 - 1.28; p = 0.044). The statistical significance of this relationship, however, did not vary by race/ethnicity or sex. Conclusions SSS independently predicts long-term smoking abstinence during a specific quit attempt. SSS may be a useful screener to identify smokers at elevated risk of relapse who may require additional attention to facilitate long-term abstinence. More research is needed to understand the mechanisms underlying the relationship between SSS and long-term smoking abstinence in order to appropriately tailor treatment to facilitate abstinence among lower SSS smokers.